A heavenly poise: radical religion and the making of the Enlightenment. Issue 1 (2nd January 2017) - Erdozain, Dominic
ABSTRACT: Scholarship continues to identify the Enlightenment with secularization, despite the theological tenor of much of the movement's canonical literature. This article proposes an explanation for such a dissonance, before addressing the matter more directly through the work of Baruch Spinoza and Pierre Bayle. The claim is that scholars have been unduly dependent upon theological commentary in reaching the fixed verdict of secularization, inferring 'atheism' and disenchantment from the polemical utterances of a privileged orthodoxy rather than the primary sources themselves. Seen apart from such controlling anathemas, icons of the radical Enlightenment such as Spinoza and Bayle emerge as deeply spiritual thinkers, challenging the theocratic assumptions of their age with theological certainties of their own, interrogating orthodoxy with a resolutely biblical rationality. The final section suggests the continuity of the eighteenth-century Enlightenment of Voltaire, Kant and Mary Wollstonecraft with the spiritual rationalism of the seventeenth century. If so many of the Enlightenment's landmark thinkers were inspired by religious ideas, the concept of a secular modernity must be open to revision.